Do health professionals tell patients what they want to know about their medicines?. (November 2018) - Young, Amber; Tordoff, June; Leitch, Sharon; Smith, Alesha
Background: Discussing medicines with patients is the responsibility of prescribers and pharmacists. However, it is not well known whether patients are given the information they want or whether information provision continues when medicines are taken long-term. Objective: To determine how often general practitioners (GPs) and pharmacists provide verbal information to patients about their medicines, and compare the information given with what patients want to know. Design: Cross-sectional surveys. Setting: New Zealand primary healthcare. Method: Two questionnaires were developed and sent to a sample of pharmacists and GPs, and chi-squared analysis was carried out. Open responses were analysed qualitatively to detect further ideas. Results: A total of 119 pharmacists and 150 GPs responded. For new medicines, significantly more GPs than pharmacists reported giving verbal information all of the time. Significantly more GPs than pharmacists reported discussing most counselling points all or most of the time. Pharmacists were more likely than GPs to discuss counselling points only when requested to by patients. For repeat medicines, significantly more GPs than pharmacists were likely to consider counselling points very important. Conclusion: Patients may not be receiving the information they want to know about their medicines, and there may be an overall lack of verbal communication about medicines with patients. Some information will only be discussed if the patient actively requests it; the likelihood of this increases with repeat medicines. The use of counselling aids and tools, such as a medicine information leaflet, could help healthcare providers provide patients with the information they need.